STRATEGIES TO DEAL WITH EPIDEMICS USING A SYSTEM DYNAMICS MODEL: A COVID-19 STUDY CASE - Lucena, Alvimar; Belderrain, Mischel Carmen Neyra (Pesquisa Operacional para o Desenvolvimento, 2021)
This paper presents a System Dynamics Model to verify well-known strategies to deal with the COVID-19 outbreak, based on the classical epidemiological SIR model. Three main strategies were tested, considering the idealized main goal of public policies, to save lives. In addition, the authorities' reaction time on implementing actions to control the pandemic is analyzed. From the tested strategies, between quarantine extension, vertical quarantine, and identification of infected persons, the most promising is to identify infected persons and the least suitable is vertical quarantine. Also, the simulations indicated that tightening quarantine at any time tends to save lives, but late action by authorities can bring overpressure on a country's health care system, which has also direct impact on the lethality of the epidemic.